Earnings Management and Tax Aggressiveness in Indonesia (Study on manufacturing companies listed on the Indonesian Stock Exchange for the period 2020-2022) - Ni Kadek Jessica Yolanda Dewi; Eni Indriani (Cita Konsultindo Research Center, 2024)
The study aims to test the impact of earnings management on tax aggressiveness in manufacturing companies by reducing pre-tax profits. The size of the profits obtained will determine the amount of tax expense paid by the company based on the tax rate imposed on those profits. The study was conducted on 43 companies that were selected by means of non-probability sampling methods using purposive sampling. Data analysis uses Pearson's correlation approach. Research findings show that earnings management has no significant impact on tax aggressiveness in a negative direction. This means that the lower the corporate tax aggressiveness, the higher the company's tendency to manage earnings by reducing profits. Companies cannot increase profits through earnings management at the same time as tax aggressiveness, thereby reducing corporate profits to reduce the tax expense to be paid. So increases and decreases in earnings management are a relationship or a condition of a trade-off that cannot occur simultaneously. The research is expected to provide information related to the profile of tax aggressiveness in manufacturing companies, so it can serve as a guideline in formulating management policies for companies.